Pengaruh dukungan keluarga terhadap kepatuhan minum obat pada pasien hipertensi di Puskesmas Tatelu - Margareth Sutjiato; Thirsa Mongi; Esther Lontoh (UNIVERSITAS SAM RATULANGI, 2026)
Background: Hypertension is a non-communicable disease with increasing prevalence in Indonesia, particularly in North Sulawesi. Medication adherence is a key factor in blood pressure control and prevention of complications. Family support plays an important role in influencing patient adherence to long-term treatment. Aim: To analyze the influence of family support on medication adherence in hypertensive patients at Tatelu Primary Health Center, North Minahasa Regency. Methods: An observational analytic study with cross-sectional design was conducted involving 60 hypertensive patients at Tatelu Primary Health Center during February 2026. Total sampling was used. Data were collected using a Likert-scale family support questionnaire (11 i t e m s ) and the validated MMAS-8 instrument. Data analysis was performed using Spearman's rho correlation test. Results: The majority of respondents had high family support (56.7%), while medication adherence was predominantly moderate (43.3%) and low (36.7%). Spearman's rho analysis revealed a significant positive correlation between family support and medication adherence (rho = 0.566; p < 0.001), indicating moderate strength of association. Conclusion: Family support has a significant positive influence on medication adherence in hypertensive patients at Tatelu Primary Health Center. Higher family support is associated with higher medication adherence, underscoring the importance of family-centered approaches in hypertension management.